Safety Features of Advanced and Economic Simplified Boiling Water Reactors - Ren-Tai Chiang (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2018)
The Advanced Boiling Water Reactor (ABWR) and the Economic Simplified Boiling Water Reactor (ESBWR) are two kinds of contemporary, advanced, commercially available nuclear power reactors. Reactor internal pumps in an ABWR improve performance while eliminating the large recirculation pumps in earlier BWRs. The utilization of natural circulation and passive safety systems in the ESBWR design simplifies nuclear reactor system designs, reduces cost, and provides a reliable stability solution for inherently safe operation. The conceptually reliable stability solution for inherently safe ESBWR operation is developed by establishing a sufficiently high natural circulation flow line, which has a core flow margin at least 5% higher than the stability boundary flow at 100% rated power of a conventional BWR, and then by designing a high flow natural circulation system to achieve this high natural circulation flow line. The performance analyses for the ESBWR Emergency Core Cooling System (ECCS) show that: (1) the core remains covered with a large margin and there is no core heat up in the ESBWR for any break size, (2) the long-term containment pressure increases gradually with time, in the order of hours, and the peak pressure is below the design value with a large margin, and (3) the margins depend on the containment volumes and water inventories. These safety design features ensure inherently safe ESBWR operation. Enhanced safety features based on lessons learned from the Fukushima nuclear accident are added in ABWR’s and ESBWR’s safety designs. The major enhancements are the further prevention of station blackout and loss of ultimate heat sink.